Nutritive values of fodders at different seasons and altitudes in Gandaki River Basin of Nepal - Shah, Manoj Kumar; Tamang, Bir Bahadur; Dhakal, Bishnu; Chaudhary, Pashupati; Shrestha, Snehi; Chhetri, Netra (Journal of Agriculture and Natural Resources, 2019)
This study aimed to assess the seasonal and ecological variation of chemical and nutritional values of locally preferred fodders in Gandaki River Basin (GRB) areas. The study was conducted in four altitudinal gradients viz. <400m, 400-800m, 800-1200m and 1200–1600m altitude above sea level in different looping seasons: rainy, spring and winter seasons. The most important five species of fodder trees Artocarpus lakoocha, Ficus roxburghii, Thysanolaena maxima, Ficus semicordata and Bauhinia purpurea were selected based on farmers’ preferences in nutritional values. Fodder samples comprised young leaves, old leaves and young twigs that were taken in July, September and December. It was revealed that nutritive value is not very much influenced by altitude but it is strongly influenced by lopping seasons. Among Thysanolaena maxima, Artocarpus lakoocha, Ficus roxburghii and Bauhinia purpurea the cellulose contents were significantly different (p<0.001) with seasons but there was no significant variation with altitudes. Similarly, Acid Detergent Fibre (ADF) contents in Thysanolaena maxima, Ficus roxburghii and Bauhinia purpurea were found significantly different with seasons. Ficus roxburghii fodder tree was found significantly different in Neutral Detergent Fibre (NDF), ADF, Cellulose and Potassium content with seasons. Similarly, fodder tree Bauhinia purpurea was found significant on Dry matter (DM), Crude fibre (CF), NDF, ADF, cellulose, tannin and potassium with seasons. The study hinted how careful planning of species selection and prudent decision in scheduling looping and feeding fodder trees can help improve animal metabolism, health, growth and productivity.